Challenging the Biomimetic Promise—Do Laypersons Perceive Biomimetic Buildings as More Sustainable and More Acceptable? - Michael Gorki; Olga Speck; Martin Möller; Julius Fenn; Louisa Estadieu; Achim Menges; Mareike Schiller; Thomas Speck; Andrea Kiesel (Biomimetics)
This study investigates whether or not laypersons perceive biomimetic buildings as more sustainable and acceptable, a notion termed the “biomimetic promise”. Employing an experimental design (N = 238), we examined assessments of three real-world biomimetic buildings at the University of Freiburg, namely the Fiber Pavilion in the Botanic Garden, the ceiling of the former zoology auditorium, and the Biomimetic Shell at the technical faculty. Participants were divided into two groups: one group was informed about the biomimetic nature of the buildings and the other group was not. Results showed no significant difference in perceived sustainability or acceptability between the two groups, favoring the hypothesis that there exists no “biomimetic bias”. Notably, with the exception of perceived sustainability comparing the pavilion and the auditorium, significant differences in assessments regarding sustainability and acceptability were observed between the buildings, emphasizing the importance of domain-specific factors in public judgments. These findings suggest that merely framing a technology as biomimetic does not inherently enhance its perceived sustainability or acceptability by laypersons. Instead, the study highlights the need for transparency and clear communication regarding sustainability benefits to gain societal acceptance of biomimetic technologies.